'If you're struggling to survive day-to-day': Class optimism and contradiction in entrepreneurial discourse. (January 2014) - Gill, Rebecca
Entrepreneurship is commonly talked about in the West as a freely chosen, optimistic occupational choice. Yet, as an ideological construct, entrepreneurship is ultimately shaped in ways that legitimize some entrepreneurs while marginalizing others. Taking cues from scholarship that has unpacked the gendered and raced dimensions of entrepreneurial discourse, this article examines the classed dimensions of such discourse. Illuminating the ideological contradiction between American dream promises of class mobility and enterprise initiatives, I argue that the hegemonic allure of entrepreneurial discourse stems in large part from the (re)production of class hierarchies around notions of exceptional capitalist ownership, action and innovation and opportunity recognition.